2022
DOI: 10.17580/nfm.2022.02.03
|View full text |Cite
|
Sign up to set email alerts
|

Processing of the zinc-lead-bearing flotation middlings by sulfidizing roasting with pyrrhotites production by predicted properties

Abstract: The accumulated amount of lead-zinc ore flotation tailings in the dumps of concentrating plants today can be considered as independent man-made deposits. In addition to their resource value as sources of lead and zinc, as well as associated gold, silver, cadmium, selenium and other metals, tailings are an environmentally hazardous source of heavy metal pollution of ground and surface waters. The environmental hazard of stale tailings is exacerbated by the fact that they occupy large areas that cannot be used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The results of previous studies [ [11], [12], [13], [14], [15], [16], [17], [18]] and the study of the characteristics of roasting products showed that sulfides of non-ferrous metals obtained by sulfidation of oxides and carbonates have high hydrophobic properties, and pyrrhotite, a product of pyrite decomposition, has a significant magnetic susceptibility. All this predetermines further methods for processing sulfidation products.…”
Section: Enrichment Of Roasting Productsmentioning
confidence: 99%
“…The results of previous studies [ [11], [12], [13], [14], [15], [16], [17], [18]] and the study of the characteristics of roasting products showed that sulfides of non-ferrous metals obtained by sulfidation of oxides and carbonates have high hydrophobic properties, and pyrrhotite, a product of pyrite decomposition, has a significant magnetic susceptibility. All this predetermines further methods for processing sulfidation products.…”
Section: Enrichment Of Roasting Productsmentioning
confidence: 99%
“…One of the most important issues is the monitoring of rock displacements in the areas of open pit fields disturbed by underground mining. Expedient solutions to such problems include analytical methods of studying the geomechanical state of the rock massif, [24,25]. Undoubtedly, the existing technologies of open pit mining of magnetite quartzite when transiting to integrated open pit-underground and subsequent underground mining of iron ore raw materials can be potential sources of man-made disasters.…”
Section: The Choice Of Object To Studymentioning
confidence: 99%
“…Clay is one of the main minerals for construction, used to produce bricks and other building materials [15,16]. The technology and main indicators of the development of these deposits are influenced by several factors: a) spatial dimensions of the deposits (length, width).…”
Section: Introductionmentioning
confidence: 99%